Green marketing mix strategy using modified measurement scales a performance on Gen Y green purchasing decision in Malaysia - Bathmathan V.; Rajadurai J. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Global goals for sustainable development is shaping the future on purchase behaviour through its trends in sustainable production and consumption. Green marketing mix strategies are seen to put an end to the conventional marketing strategies and is a path breaker that affects the value proposition that leads green purchasing decision (GPD). Thus, to reduces ecological footprint through green marketing mix strategies, this study aims to identify factors that influences young consumers to migrate to GPD. The study was conducted in two phases. Firstly, a qualitative approach was used to extract the current theme in green marketing by interviewing 5 focus groups. The themes were compared with other studies to identify the relevancy of the items and was consequently validated with experts from the relevant industrial and academic field. The final questionnaire was distributed to 200 Gen Y respondents in Malaysia. The data was analysed using the SMART PLS 3.0. The result shows that green marketing mix factors except price influence the trends on Gen Y GPD in Malaysia. The findings are very useful for marketers and manufacturers to understand, and redefining their green marketing mix strategies to meet the global sustainability goals. The fine points discussed in the findings and discussion section is also useful for organizations to implement strategies to attract green consumers to make the green purchases. BEIESP.